Peran Primer Koperasi Pengelola Sampah Dalam Pemberdayaan Masyarakat - Nurmandita, Zachra; Herdiana, Dedi; Kurniawan, Muh Idham (Tamkin: Jurnal Pengembangan Masyarakat Islam, 2023)
Waste is a crucial problem in Indonesia, the current accumulation of waste is caused by improper waste management. Primary Waste Management Cooperative (PKPS) Kab. Cianjur acts as a facilitator who presents solutions to waste problems by creating innovations in waste management and making waste as a business opportunity in empowering the community. The purpose of this study was to determine the program, process, and results obtained by the Primary Waste Management Cooperative (PKPS) Kab. Cianjur in empowering the community. The method used in this study is a descriptive method, with a qualitative approach. Data collection techniques used are observation, interviews, and documentation studies. Based on the results of the research PKPS Kab. Cianjur has been able to overcome waste problems through several programs, namely organic waste sorting, maggot cultivation, socialization/controlling, and organic waste management training/workshops to waste banks TPS 3R. The PKPS process in empowering the community goes through 4 stages, namely planning, reflection, implementation, and evaluation. The results obtained by PKPS in empowering the community consist of 3 aspects, namely economic, environmental, and social.